Revisiting Nature’s “Unifying Patterns”: A Biological Appraisal - Guillaume Lecointre; Annabelle Aish; Nadia Améziane; Tarik Chekchak; Christophe Goupil; Philippe Grandcolas; Julian F. V. Vincent; Jian-Sheng Sun (Biomimetics, 2023)
Effective bioinspiration requires dialogue between designers and biologists, and this dialogue must be rooted in a shared scientific understanding of living systems. To support learning from “nature’s overarching design lessons” the Biomimicry Institute has produced ten “Unifying Patterns of Nature”. These patterns have been developed to engage with those interested in finding biologically inspired solutions to human challenges. Yet, although well-intentioned and appealing, they are likely to dishearten biologists. The aim of this paper is to identify why and propose alternative principles based on evolutionary theory.